Evaluating the reliability of macro-economic models - Chow, Gregory C.; Corsi, Paolo; Centri di ricerca scientifica I.B.M.; Università di Pisa. (Chichester : New York : Wiley, 1982)
The IBM Scientific Center in Pisa, organised an International Symposium on Criteria for Evaluating the Reliability of Macro-economic Models. Papers presented are extremely useful for anyone who wishes to improve the reliability of one. First, one should appeal to economic theory to judge the reasonableness of model specifications. Also, one can compare the model with alternative formulations, using appropriate statistical criteria for choosing among them.
Papers presented at the International Symposium on Criteria for Evaluating the Reliability of Macro-economic Models, held Dec. 16-18, Pisa, Italy, organized by the IBM Scientific Center of Pisa and sponsored by the University of Pisa.
Includes bibliographical references and index.
II 15/01/2019
Loans
Keywords: Econometrics; Macroeconomics; Economics